Lifting the fog of peace : how Americans learned to fight modern war - Davidson, Janine (The University of Michigan Press, 2010)
Counterinsurgency and stability operations in Iraq and Afghanistan are only the most recent examples of the U.S. Armed Forces fighting insurgents, building infrastructure, enforcing laws, and governing cities. For more than two centuries, these assignments have been a regular part of the military's tasks; yet until recently the lessons learned from the experiences have seldom been formally incorporated into doctrine and training. As a result, each generation of soldiers has had to learn on the job. Janine Davidson traces the history of the U.S. military's involvement in these complex and frustrating missions. By comparing the historical record to the current era, Davidson assesses the relative influence of organizational culture and processes, institutional structures, military leadership, and political factors on the U.S. military's capacity to learn and to adapt. Pointing to the case of Iraq, she shows that commanders serving today have benefited at the tactical level from institutional changes following the Vietnam War and from the lessons of the 1990s. Davidson concludes by addressing the question of whether or not such military learning, in the absence of enhanced capabilities and capacity in other U.S. government agencies, will be sufficient to meet the complex challenges of the 21st century. --From publisher's description.